Analisis Struktur Dan Nilai Moral Dalam Film Jembatan Pensil Serta Pemanfaatanya Sebagai Bahan Ajar Di Tingkat SMA Kelas XI - Laksmita Nur Afiati; Wida Widyawati; Ricky Sukandar; Burhan Sidik (Journal on Education, 2024)
This research examines the structure and moral values ​​in the film Pencil Bridge by Hasto Broto. Films have many benefits that we can take, because a film can be used as a life lesson. Researchers want to reveal the moral values ​​contained in the film Pencil Bridge by Hasto Broto. The objectives to be achieved in this research are: (1) Describe the elements in the form of plot, characterization, setting and theme in the film Pencil Bridge by Haasto Broto. (2) Describe the form of moral values ​​in the film Pencil Bridge by Hasto Broto. (3) Utilization of research results on the film Pencil Bridge by Hasto Broto as teaching material in class XI high school. The findings of this research are, (1) The structure of the film Jembatan Fensil by Hasto Broto consists of theme, plot, characters, setting, message (2) The moral value in the film Jembatan Pensil by Hasto Broto is the relationship between humans and themselves, the relationship between humans and humans. fellow humans in the social and natural environment as well as human relationships with God (3) Study of the film Pencil Bridge by Hasto Broto as teaching material for Indonesian language learning in class XI.